Improvement of the productivity of "Caramelo variety" peanuts (Arachis hypogaea) applying different doses of Evergreen biostimulant - Macias Vera, Ámbar Yerely; Saucedo Aguiar, Álvaro Edmundo; Sánchez Iznaga, Ángel Lázaro; Pazmiño Muñoz, Edison Marcelo; Camacho Bustamante, Luis Carlos (Ingeniería Química y Desarrollo, 2024)
The objective of the present investigation was to determine the increase in the productivity of the peanut crop "Caramelo variety" (Arachis hypogaea), through the use of different doses of Evergreen biostimulant. The investigation was carried out in the Los Ríos province. In order to fulfill the proposed objectives, a randomized complete block experimental design was carried out, with four treatments and four repetitions of 20 square meters each repetition, with a distance of 4x5 m. For the collection of information, six agronomic variables were evaluated, which were taken from each repetition using a sample of 10 peanut plants, and then these averaged data were subjected to ANOVA statistical analysis, and finally a Tukey test was applied to 95% of probability. The results showed that treatment 4 (Evergreen 2 L/ha) had a better effect on the agronomic variables evaluated, where the highest plant height obtained was 32.3 cm, the number of pods per plant was 42.20, the production per plant was 151.43 g/plant, the root length was 21.38 cm, the weight of 100 grains was 85.25 g and the highest yield was 4,403.43 kg/ha.
Keywords: Productivity; doses; economic encome; increase; biostimulant